RADIOACTIVE IRON AND ITS EXCRETION IN URINE, BILE, AND FECES - Hahn, P. F. (The Rockefeller University Press, 1939)
Radioactive iron as ferrous gluconate given by vein enables us to study iron excretion in urine, bile, and feces. There is an initial extra output in urine and feces during a few days (3 to 15 days) following the iron injection and this may total 2 to 8 per cent of the injected iron. Following this initial reaction the urinary excretion of radio-iron drops to traces or even to zero. The feces always contain measurable amounts of radio-iron—in five dogs receiving 100 to 250 mg. of radio-iron the fecal excretion per day settled down to 0.05 to 0.4 mg. per day. Blood destruction (acetyl-phenylhydrazine) causes a definite increase in radio-iron eliminated in the feces (0.1 to 1.0 mg. per day). Probably most of this excess iron comes through the biliary tract (bile fistula). The bile under usual conditions contributes very little iron to the intestine (0.01 mg. radio-iron per day or less). The body controls its iron stores by absorption or lack of it rather than by its capacity to eliminate it. The evidence is overwhelming that the dog excretes iron with difficulty and in small amounts (even in the plethoric state) by means of the biliary and gastro-intestinal tracts.